To solve the quadratic equation \( 49x^2 = -392x - 784 \) using the perfect square trinomial pattern, let’s first rearrange the equation in standard form:
\[ 49x^2 + 392x + 784 = 0 \]
Next, we notice that this quadratic can be factored by identifying a perfect square trinomial. We can rewrite the left-hand side:
\[ (7x + 28)^2 = 0 \]
To see how we reached this, we recognize that:
\[ (7x + 28)(7x + 28) = 49x^2 + 392x + 784 \]
Now, we set the factor equal to zero:
\[ (7x + 28) = 0 \]
Solving for \(x\):
\[ 7x = -28 \] \[ x = -4 \]
Hence, the solution to the quadratic equation \( 49x^2 = -392x - 784 \) is:
x = -4.
Therefore, the correct response is:
x = -4.